2018
DOI: 10.1093/nar/gky046
|View full text |Cite
|
Sign up to set email alerts
|

Structural analyses of NEAT1 lncRNAs suggest long-range RNA interactions that may contribute to paraspeckle architecture

Abstract: Paraspeckles are nuclear bodies that regulate multiple aspects of gene expression. The long non-coding RNA (lncRNA) NEAT1 is essential for paraspeckle formation. NEAT1 has a highly ordered spatial organization within the paraspeckle, such that its 5′ and 3′ ends localize on the periphery of paraspeckle, while central sequences of NEAT1 are found within the paraspeckle core. As such, the structure of NEAT1 RNA may be important as a scaffold for the paraspeckle. In this study, we used SHAPE probing and computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 52 publications
8
129
0
1
Order By: Relevance
“…It is unclear how the localization of BRG1 in these “patches” correlates with its known ability to assembly paraspeckles (Kawaguchi et al, ). Both the electron microscopy and SRM data show that NEAT1 folds in half, with the 5′ and 3′ ends positioned in the outer shell, and the middle of the RNA in the inner core, which correlates with the self‐interaction data summarized above (Lin et al, ; Souquere et al, ; West et al, ). This correlates well with recent research that indicates the NEAT1 lncRNA middle domain is essential for NONO and SFPQ recruitment, and phase separation (Yamazaki et al, ).…”
Section: Various Nuclear Bodies Exhibit Rna‐related Functional Architsupporting
confidence: 70%
See 1 more Smart Citation
“…It is unclear how the localization of BRG1 in these “patches” correlates with its known ability to assembly paraspeckles (Kawaguchi et al, ). Both the electron microscopy and SRM data show that NEAT1 folds in half, with the 5′ and 3′ ends positioned in the outer shell, and the middle of the RNA in the inner core, which correlates with the self‐interaction data summarized above (Lin et al, ; Souquere et al, ; West et al, ). This correlates well with recent research that indicates the NEAT1 lncRNA middle domain is essential for NONO and SFPQ recruitment, and phase separation (Yamazaki et al, ).…”
Section: Various Nuclear Bodies Exhibit Rna‐related Functional Architsupporting
confidence: 70%
“…The NEAT1 lncRNA gene product is multivalent and interacts directly with various paraspeckle proteins, which mediates paraspeckle nucleation and supports the hypothesis that this nuclear-retained RNA is essential for their formation (Clemson et al, 2009;Sunwoo et al, 2009). However, a recent study has suggested that long-range contacts between the 5 0 and 3 0 ends of NEAT1 RNA also contribute to paraspeckle structure (Lin, Schmidt, Bruchez, & McManus, 2018). Many paraspeckle proteins contain prion-like IDR domains, contributing to the ability to form large, phase-separated condensates in the nucleus and hydrogels in vitro (Hennig et al, 2015;Schwartz et al, 2013).…”
Section: Paraspecklementioning
confidence: 99%
“…As stated above, ONT and PacBio can perform long read cDNA sequencing [260] and even more exciting, both technologies can perform direct long read RNA sequencing [261,262]. The beauty and simplicity that ONT and PacBio offers is the ability to sequence the full expressed isoform (cDNA and direct RNA), without worries of misidentifying a complex splicing pattern, RNA cleavage events and also not relying on transcript annotation files will lead to the identification of novel isoforms which are problems faced using short-read Illumina sequencing.…”
Section: Alternative Splicing Of Lncrnasmentioning
confidence: 99%
“…Investigations of lncRNA secondary structure and tertiary structure have revealed methods of epigenetic and post-transcriptomic regulation [38,46] and may further implicate lncRNA's influence over alternative splicing. Thereby, we propose that lncRNAs like RP5-1148A21.3 may interact intramolecularly and alter post-transcriptional gene regulatory networks.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, subnuclear bodies have shown promise in understanding lncRNA's potential in creating other cellular machinery [37], and lncRNAs which bind to many RBPs could be recruiting those proteins to form a subnuclear body. Groups invested in mechanisms of post-transcriptional regulation may begin to examine RBP binding data, and multiple sequence alignment of lncRNAs in order to understand intramolecular interactions in subnuclear bodies and secondary lncRNA structure [38,39]. Hence, further attempts to understand non-coding RNA structure, should account for interactions of lncRNAs and RBPs inside of the nucleus and in the cytoplasm in order to reveal other means of lncRNAs' involvement in splicing.…”
Section: Discussionmentioning
confidence: 99%